Unveiling the Relationship Between L2 Utterance Fluency and Perceived Fluency in Monologic and Dialogic Speaking. - Gao, Jianmin; Sun, Peijian Paul (Language & Speech, 2026)
The study explored the relationship between L2 utterance fluency and perceived fluency in monologic and dialogic speaking. A total of 136 Chinese university English learners with diverse L2 proficiency levels and three experienced raters participated in the study. The study employed a mixed-methods approach integrating quantitative (regression analysis) and qualitative (stimulated recalls) analyses. In the monologic task, all utterance fluency dimensions (speed, breakdown, and repair fluency measures) significantly predicted perceived fluency ratings, except for filled pause rate and false start rate. Breakdown fluency measures, particularly silent pause measures, had the most substantial impact on perceived fluency ratings. In the dialogic task, breakdown fluency emerged as the sole significant predictor for perceived fluency scores, overshadowing the predictive impact of speed and repair fluency measures. The temporal measure of turn-taking did not significantly affect perceived fluency scores. Stimulated recalls were generally consistent with the quantitative results and revealed additional factors—content quality, pronunciation, and comprehensibility—that influenced fluency perceptions. The study highlighted the contextual effect on the relationship between utterance fluency and perceived fluency, suggesting that L2 speaking proficiency rating rubrics should be adjusted to account for differences between monologic and dialogic speaking.